Expansion of composite tubes - Lee, Jwo Tyng. (2011)
In this report, aluminium alone, aluminium with glass fibres coated with polyurethane, steel alone and steel with glass fibre coated with polyurethane were used for experimentation. Expansion die of diameter 65mm (1.4e) and 70mm (1.5e) with angle of 40° were also used on both aluminium and steel in this experiment.